PROPOSED CONCEPTUAL FRAMEWORK OF INVENTORY MANAGEMENT USING THE JUST-IN-TIME (JIT) PHILOSOPHY - Eduardus Tandelilin (Faculty of Economics and Business, Universitas Gadjah Mada, 1996)
The effectiveness of the proposed JIT inventory management model, while conceptually developed based on previous case studies, depends largely to both internal and external support mechanisms of the organization. While the JIT philosophy has manifested remarkable contributions to productivity and efficiency in the developed countries, much has yet to be gained from it in the developing countries. Some problems can confound the adoption and implementation of JIT in the third world.Sector, as in the case of Tanzania (Msimangin, 1993): financial constraints, inadequate supply of inputs required for the production mills to operate near capacity, international delivery delays, an inadequate transportation infrastructure, and unreliable product demand forecasts. These problems are also present in the Philippines. Zamora (1989) identified several additional problems encountered in the implementation of JIT components in the Philippine setting: resistance to change, socio-cultural barriers, and lack of training, The success of any model or framework using the JIT philosophy must address these prob- j lems firmly. As in other cases, the successfti implementation of the proposed inventory management framework using the JIT philosophy could be achieved if existing local conditions aw considered to suit the requirements of the model] Flexibility of model adoption is therefore necessary.Further, it is recommended that the proposed model be practically applied in applicable situations and empirical informal be obtained to improve the framework. In this sense, the proposed model will be tested as to its practical usefulness apart from being conceptual.